Housing Speculation and Housing Price Bubbles in Korea - Chung, Hee Soo (Joseph); Kwon, Hyuk Il (International Journal of Property Sciences (E-ISSN: 2229-8568), 2016)
One of the major social and economic problems in Korea in recent years has been and still is the sustained housing prices spiral, especially since 2000. In Seoul, the ratio ofhousing pricesto household annual income is about 10 times. This is three or four times higher than the corresponding ratios in advanced countries. To make the matter worse, housing prices continue to rise rapidly in large cities including Seoul (up to twenty per cent per year lately). The excessively high housing prices results in worsening housing affordability, higher wage rates and worker's weakening desire to work. It is a common belief in Korea that speculation is the main reason for such high housing prices, thus the government has applied a series of anti-speculative measures including major increase in capital gains tax and property tax. However, these measures have not been able to eliminate speculative housing prices bubbles. This paper is designed on one hand to evaluate the contribution of speculative activities to housing prices hike and, on the other to verify the presence of bubble in housing prices. In order to quantify the impact of speculation on housing prices, a simple devise is applied; the value of the explained variation of housing prices resulting from a regression analysis is decomposed into the percentage share of each independent variable including the variable for speculation. The presence of bubble is verified through three estimation methods: the long-run.